Carboxylation of Organoboronic Esters Catalyzed by N-Heterocyclic Carbene Copper(I) Complexes - Ohishi, Takeshi; Nishiura, Masayoshi; Hou, Zhaomin (Angewandte Chemie International Edition, 2008)
Copper complexes with a CO2 fixation: Copper(I) complexes serve as excellent catalysts for the carboxylation of aryl‐ and alkenylboronic esters with CO2, affording a variety of functionalized carboxylic acid derivatives (see scheme). Important active intermediates such as the copper(I) aryl and carboxylate complexes, [(IPr)CuR] and [(IPr)CuOCOR] (R=4‐MeOC6H4, IPr=1,3‐bis(2,6‐diisopropylphenyl)imidazol‐2‐ylidene), are isolated and structurally characterized.